Night-time gravity waves detected with multi-frequency airglow imager - Machubeng, Karabo Pebane (Rhodes University, Faculty of Science, Department of Physics and Electronics)
This thesis shows the statistics of atmospheric gravity waves (AGWs) observed in the OI emission 557.7 nm at _97 km altitude using an all-sky imager based in Sutherland, South Africa (32.37_ S, 20.81_ E) in the year 2017. The wavelengths were determined using the propagation vector method, velocity was determined using the cross correlation of 1D FFT and the period was determined using the equation that relates wavelength and velocity. It was found that the horizontal wavelength in summer was almost evenly distributed between 10 and 40 km and for autumn, winter and spring were mostly between 10 and 30 km. The favoured speeds were between 40 and 50 m/s in autumn, as well as 30 and 50 m/s in summer, but the AGWs in winter had a bimodal speed distribution of 20 - 40 and 50 - 70 m/s. The majority of periods observed in all seasons were less than 20 minutes with a dominant peak of 5 - 10 minutes in autumn and spring. There was no favoured propagation direction for spring, but AGWs favoured a southeastward propagation in summer, and a southward propagation in autumn and winter.
Keywords: Gravity waves; Airglow; Gravity waves -- Seasonal variations; All Sky Imager